Dynamic forward error correction in wireless real‐time Internet of Things networks. Issue 6 (1st November 2017) - Herrero, Rolando; St‐Pierre, Claude
Abstract : Wireless sensor and actuator networks (WSAN) have greatly benefited from the latest development in real‐time Internet of Things standardisation efforts. Specifically, the Internet Engineering Task Force Constrained Application Protocol (CoAP) is one of the preferred mechanisms that provide session transport in the context of low‐power low‐rate networks in general and WSAN in particular. CoAP, that relies on traditional user datagram protocol, introduces a particular mode of operation, known as non‐confirmable, that minimises latency but it is highly sensitive to network packet loss. The use of forced forward error correction (FEC), although efficient at reducing packet loss, excessively increases the session throughput. The authors introduce an algorithm that dynamically manages FEC minimising application layer packet loss while keeping throughput under control. The mechanism is evaluated through an experimental framework where traditional CoAP, forced FEC CoAP and dynamic FEC CoAP implementations are compared.